How is continuity of care experienced by people living with Chronic Kidney Disease? - Brand, Sarah; Pollock, Kristian (Wiley, 2017)
Aims and objectives: To explore patients’ perceptions of continuity of care within a hospital-based specialist service. Background: Patient journeys through health care are becoming increasingly complex. For patients with chronic conditions, the longevity of their illness and common multiple co-morbidities make this complexity more pronounced. Continuity of care is most challenging to provide for these patients. A multifaceted model of continuity is widely accepted, but despite this, much literature focuses exclusively on relational aspects. In addition, the majority of the literature has focused on primary and family care settings whilst continuity within specialist and hospital care has not been widely researched. Design: A qualitative descriptive design was used. Methods: Thirteen semi-structured interviews with patients accessing services as at a Renal and Transplant Unit at a UK hospital were conducted in 2014. Data were analysed thematically to identify commonality as well as diversity amongst participants. Results: Five themes of time, being known, knowledge, knowing the system and responsibility were identified within patient experiences of continuity. The multidisciplinary team was more important in relational continuity than literature has previously suggested. Patients’ expectations in relation to continuity were notably different in their interactions with hospital-based services in comparison with community and family-based care. Conclusions: Patients accessing specialist care services may perceive continuity differently to those receiving care in the community. Generic guidance concerned with patient experience outcomes may be difficult to implement in practice. Relevance to clinical practice: Nurses and the wider healthcare team play a fundamental role within the provision of continuity, even in predominantly medically led specialist services. The differences between primary and secondary care in terms of patient expectation and experience should be recognised to ensure effective models of care are implemented which both meet patient expectations and improve their experience of care.